Germination inhibitory activity of aqueous extracts of native grasses from South America - Scrivanti,Lidia Raquel (2021)
Abstract Soluble allelochemicals have generated great interest since they can be used for the biological control of pests, especially of weeds. However, few studies have evaluated the effectiveness of soluble compounds of exudates on germination in relation to exposure time. Here we evaluate the inhibitory effect of aqueous root, stem and leaf extracts of five South American species of Bothriochloa on the percentage of seed germination of four target species (lettuce, lovegrass, maize and wintergreen paspalum) over three exposure periods (48, 120 and 168 h). Aqueous extracts of the five Bothriochloa species inhibited germination; germination inhibition was strongly correlated with exposure time, with the longest treatment period (168 h) being the one of greatest inhibitory activity. Inhibitory activity differed among types of aqueous extracts. The suitable management of allelopathy might improve crop productivity and environmental protection through biologically friendly control of weeds.